Technology and Standardization Strategies Related to The Diffusion of Smart Houses: The Case of ECHONET in Japan - Kumiko Miyazaki; Kentaro Nishida (STI Policy and Management Journal, 2016)
In this paper, an analysis is made of the technology and standardization strategies regarding ECHONET and KNX, which are the de jure standards for smart houses in Japan and Europe. Eleven interviews with the main actors related to the ECHONET Consortium and KNX were conducted. Three research questions were set. What are the technology strategy related concerns of the main actors related to ECHONET? What are the issues related to the diffusion of smart houses? What are the underlying strengths and weaknesses of ECHONET when compared with KNX? The analyses showed that the strategies of the various actors towards the diffusion of smart houses were different, based on their different perspectives, visions and competences. A comparison between Japanese and European case highlighted the different standardization strategies and areas of focus. The main bottlenecks towards the diffusion of smart houses were identified.